Study on soil corrosion principles of the Q235 steel ground net in Weinan Shaanxi - Yan Aijun; Hou Juanling; Chen Yi; Feng Lajund (Фізико-хімічна механіка матеріалів, 2011)
In order to on-line detect the ground grid corrosion, the relationship between the corrosion rate of Q235 steel and electrical resistance was studied by an accelerated corrosion in the soil where a 750 kV high-voltage transformer substation was established. The corrosion products and morphology were characterized by SEM (scanning electron microscopy) and XRD (X-ray diffraction). The results show that the rusty layer by the accelerated corrosion has the same structure as that by natural corrosion, and the corrosion products consisted mainly of γ-Fe₂O₃ and Fe₃O₄. One-year monitoring was conducted and the relationship of the corrosion rate (V) and the resistivity (R) was established. The error between the nature corrosion rate and the calculated corrosion rate is less than 3%.